Reaction of different rock types to low-power (3.2 kW) microwave irradiation in a multimode cavity. (15th March 2018) - Hartlieb, P.; Kuchar, F.; Moser, P.; Kargl, H.; Restner, U.
Graphical abstract: Highlights: A study on microwave treatment of different rock types is presented. The influence is assessed by geochemistry, XRD and p-wave velocity. Heating characteristics range widely with mineralogy and water content. Heating is linked to geo-chemical and mineralogical changes. Well-absorbing rocks melt and crack extensively as result of microwave irradiation. Abstract: This study deals with low-power (3.2 kW) microwave irradiation of a range of rocks and provide an indication of the suitability of certain rock types for this treatment method for rock fragmentation and mineral comminution. The influence of microwave irradiation was assessed physically by measuring rock properties and observing cracking phenomena and chemically by analysing the mineralogical and chemical composition before and after microwave irradiation. The results show that the reaction to microwave irradiation strongly depends on the mineralogy or the water content of the rock. Rocks with low content of microwave absorbers (like granite and sandstone) heat slowly and do not show strong physical changes, whereas rocks with better microwave absorption (basalt, mafic volcanites) heat quickly leading to significant physical changes. It is apparent that the presence of water either in the porous volume of the rock or in the mineralogical structure (e.g. clay minerals) adds to the destructive work with the help of the generated steam pressure.